Living al-Qur’an dan Hadis: Pendekatan Filsafat Pragmatisme Charles Sanders Peirce - Sulaiman, Akhmad; Shofi'i, Eri Nur (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2020)
This article aims to describe the relevant theories of Charles Sanders Peirce's pragmatism philosophy and explain how these theories work in the research of the living Qur'an and hadith. It is encouraged by the lack of this research on aspects of philosophy. The significance of the theories is that the research, besides focusing on the rituals or traditions in a particular community, also focuses on the belief. The position of the agent in this research becomes very significant because the social phenomena that are the object of the research are manifestations of his subjective interpretations. It is the advantage of these theories compared to the applied sociological and anthropological theories. Peirce's pragmatism philosophy directs researchers to target the belief aspect as well as the practical aspect of research with the sociology and anthropology approach. The belief includes how subjects believe what they practice and how the belief is constructed. At this point, Peirce's pragmatism philosophy notice how the agent interprets texts subjectively to produce traditions in society. The ritual changes is also a research concern because it is part of the dynamics of pragmatic meaning. Keywords: Pragmatism Philosophy, Peirce, Living al-Qur’an and Hadith.   Abstrak Artikel ini bertujuan untuk mendeskripsikan teori-teori relevan dari filsafat pragmatisme Charles Sanders Peirce (1839-1914) dan menjelaskan bagaimana teori-teori ini bekerja dalam penelitian living al-Qur’an dan hadis. Ini didorong oleh kekurangan penelitian ini pada aspek filsafat. Signifikanisi filsafat pragmatisme Peirce adalah bahwa penelitian, selain fokus pada sisi ritual-ritual atau tradisi-tradisi dalam komunitas tertentu, juga fokus pada keyakinan. Kedudukan agen dalam penelitian ini menjadi sangat signifikan karena fenomena sosial yang menjadi objek penelitian merupakan manifestasi dari interpretasi subjektifnya. Ini merupakan kelebihan dari filsafat pragmatisme dibanding teori-teori sosiologi dan antropologi yang telah diterapkan. Keyakinan meliputi bagaimana subjek-subjek meyakini apa yang mereka kerjakan dan bagaimana terbentuknya keyakinan tersebut. Pada titik ini, filsafat pragmatisme Peirce memperhatikan bagaimana agen memaknai teks secara subjektif untuk menghasilkan tradisi-tradisi di dalam masyarakat. Perubahan-perubahan ritual juga menjadi perhatian penelitian kerena itu merupakan bagian dari dinamika makna pragmatis. Kata Kunci: Filsafat Pragmatisme, Peirce, Living al-Qur’an dan Hadis.